Single Versus Multidrug Regimen for Surgical Infection Prophylaxis in Left Ventricular Assist Device Implantation. Issue 6 (November 2018) - Aburjania, Nana; Ertmer, Brennan M.; Farid, Saira; Berg, Melody; Nienaber, Juhsien J. C.; Tchantchaleishvili, Vakhtang; Stulak, John M.; Baddour, Larry M.; Sohail, Muhammad R.
Abstract : Infection is a serious complication of left ventricular assist device (LVAD) therapy. However, an optimal antimicrobial surgical infection prophylaxis (SIP) regimen for LVAD implantation is not well established. We retrospectively reviewed all adults who underwent continuous-flow LVAD implantation from February 2007 to March 2015 at Mayo Clinic Rochester. Left ventricular assist device infection (LVADI) was defined using criteria published by the International Society for Heart and Lung Transplant. Patients excluded from the analysis included those who did not have HeartMate II or HeartWare device, patients with incomplete documentation of SIP, and those with an actively treated infection at the time of LVAD implantation. We compared risk of LVAD-specific and LVAD-related infections and all-cause mortality between SIP regimens at postoperative day 90 and 1 year using Kaplan–Meier time-to-event analyses. During study period, 239 adults underwent continuous-flow LVAD implantation at our institution where 199 patients received single-drug and 40 received multidrug SIP regimen. Median patient age was 62 years. Left ventricular assist device infection occurred in three patients (1.5%) in the single-drug group versus two patients (5.0%) in the multidrug group at 90 days ( p = 0.4). There was no difference in infection-free ( p = 0.4) and overall survival ( p = 0.9) between two groups at 1 year. In conclusion, there was no clear benefit of using multidrug regimen as it did not impact infection-free survival or all-cause mortality compared with single-drug regimen. Prospective clinical trials are needed to further define the optimal SIP regimen for LVAD implantation.